Characteristics of peptide assimilation by Helicobacter pylori : Evidence for involvement of cell surface peptidase - YUN, Soon-Kyu; CHOI, Kyung-Min; UHM, Chang-Sub; PARK, Jeong-Kyu; HWANG, Se-Young (Journal of microbiology and biotechnology, 2005)
Peptide assimilation by Helicobacter pylori wasinvestigated using L-phenylalanyl-3-thia-phenylalanine (PSP)as a detector peptide; the release of thiophenol upon enzymatichydrolysis of PSP was spectrophotometrically detected withthe aid of 5,5'-dithiobis[2-nitrobenzoic acid] (DTNB). By addingPSP to whole-cell suspension, thiophenol was producedprogressively, resembling that found in Esherichia coli orStaphylococcus aureus. Interestingly, the rate of thiophenolproduction by H. pylori in particular was markedly reduced whencells were pretreated with trypsin, indicating surface exhibitionof peptidase. According to the competitive spectrophotometryusing alanyl-peptides, H. pylori did not appear to assimilatePSP through the peptide transport system. No discernible PSPassimilation could be ascertained in H. pylori cells, unlessprovided with some additives necessary for peptidase activity,such as Ni2+ or Mg2+ and an appropriate concentration ofpotassium or ammonium salts. These observations stronglysuggest that, regardless of a presumptive peptide transportsystem, peptide assimilation of H. plori appears to be highlydependent upon milieu conditions, due to unique peptidaseexhibition on the cell surface. KCI Citation Count: 3